Pengaruh pemberian smoothies belima terhadap tekanan darah sistolik dan diastolik Peserta Posbindu Cikokol Kota Tangerang - Sofia Harnum (ARGIPA (Arsip Gizi dan Pangan), 2020)
ABSTRACT Patients with hypertension will live life, depend on drugs that often cause side effects. This research provides an alternative in overcoming hypertension using natural ingredients to minimize side effects, namely by giving belima smoothies (star fruit, banana, cinnamon, and dragon fruit) containing 250 ml of fiber and potassium. This type of research is experimental with one group pre-test post-test design. This research method uses the total sampling method. This study’s purpose was to determine the differences in systolic and diastolic blood pressure on the administration of belima smoothies to participants in Posbindu Cikokol Tangerang City. The subjects in this study were 32. Data were analyzed by the Paired t-test and Wilcoxon test. There were significant differences between before and after Belima smoothies intervention. The rate of systolic blood pressure was lower from 143 mmHg to 127 mmHg. The rate of diastolic blood pressure was lower from 90 mmHg to 80 mmHg. Sodium intake was lower from 4,825 mg to 2,881.2 mg, potassium intake increases from 1,020.8 mg to 1,625, 4 mg and fiber intake also increase from 7.2 g to 11.6 g. Keywords: Banana, Cinnamon, Dragon Fruit, High Blood Pressure, Star fruit